INTELLIGENT SIMULATOR SYSTEMS AS A BASIS DEVELOPMENT OF AVIATION OF UKRAINE - Lastovchenko , M. M. (Problems of Informatization and Management, 2005)
A fundamentally new approach to the training of basic categories of personnel for aviation is considered. A conceptual model of an intelligent system of simulators is proposed.